Utero-cutaneous fistula following cesarean section: A case report - Abdelhamid Jadib, MD (Elsevier, 2022)
Utero-cutaneous fistula is a rare pathology. It mostly occurs consecutively to surgical intervention such as Cesarean section. Blood discharge from the cesarean scar during menstruation is a quasi-pathognomonic feature. Imaging modalities, particularly with the injection of contrast material through the cutaneous fistulous opening, confirm the diagnosis. The management is mainly surgical.We report the case of a utero-cutaneous fistula in a 27-year-old lady, with systemic lupus erythematosus. She presented seven months after her third cesarean section with pain and blood discharge from the cutaneous scar during menstruation for four months. A pelvic CT scan with the injection of the contrast material through the cutaneous fistulous opening confirmed the diagnosis of utero-cutaneous fistula. Surgical management was successful.